Evolution of HOD and galaxy properties in filaments and nodes of the cosmic web - Perez, Noelia Rocío (2024)
We study the evolution of the Halo Occupation Distribution (HOD) and galaxy properties of nodes and filamentary structuresobtained by DisPerSE from the Illustris TNG300-1 hydrodynamical simulation, in the redshift range 0 ≤ ≤ 2. We computethe HOD in filaments and nodes and fit the HOD parameters to study their evolution for both faint and bright galaxies. In nodes,the number of faint galaxies increases with decreasing redshift in the low mass halos, while no significant differences are seenin high mass halos. Limiting the HOD to bright galaxies shows that halos increase in mass more than the number of brightgalaxies they accrete. For filaments, no large differences in HOD are found for faint galaxies, although for brighter galaxies thebehaviour is the same as in nodes. The HOD parametrization suggests that filaments have no effect on the mass required to hosta galaxy (central or satellite), whereas nodes do. The results of the study indicate that with this parametrization, filaments do notseem to affect the stellar mass content of galaxies. In contrast, nodes appear to affect halos with masses below approximately1012.5 ℎ−1 ⊙ at local redshift. The analysis of the galaxy colour evolution shows a reddening towards lower redshift, althoughthese processes seem to be more efficient in massive halos, with a strong effect on bright galaxies. The general evolution suggeststhat the building of galaxy population within halos is influenced by both the accretion of faint galaxies and the mass growth ofthe bright ones.